2021
DOI: 10.3390/ijms22157862
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Double Treatment with Adult-Sourced Adipose-Derived Mesenchymal Stem Cells Increases Striatal Medium-Spiny Neuronal Number, Decreases Striatal Microglial Number, and Has No Subventricular Proliferative Effect, after Acute Neonatal Hypoxia-Ischemia in Male Rats

Abstract: Perinatal hypoxia-ischemia (HI) is a major cause of striatal injury. Delayed post-treatment with adult-sourced bone marrow-derived mesenchymal stem cells (BMSCs) increased the absolute number of striatal medium-spiny neurons (MSNs) following perinatal HI-induced brain injury. Yet extraction of BMSCs is more invasive and difficult compared to extraction of adipose-derived mesenchymal stem cells (AD-MSCs), which are easily sourced from subcutaneous tissue. Adult-sourced AD-MSCs are also superior to BMSCs in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…Several pieces of experimental evidence support the idea that the transplantation of MSCs is associated with an improvement in synaptic plasticity [49][50][51][52][53][54][55]. MSCs have also been reported to ameliorate cognitive performance in different animal models of NDDs, including AD [56][57][58][59][60][61][62], thus suggesting that this can represent a promising therapeutic strategy.…”
Section: Cell Therapy In Alzheimer's Diseasementioning
confidence: 90%
“…Several pieces of experimental evidence support the idea that the transplantation of MSCs is associated with an improvement in synaptic plasticity [49][50][51][52][53][54][55]. MSCs have also been reported to ameliorate cognitive performance in different animal models of NDDs, including AD [56][57][58][59][60][61][62], thus suggesting that this can represent a promising therapeutic strategy.…”
Section: Cell Therapy In Alzheimer's Diseasementioning
confidence: 90%
“…Some of the stereological methods used were not computerized, yet they are still valid practical approaches [52]. It is acknowledged that computerized approaches are more common now (e.g., [84]).…”
Section: Stereological Analyses Of the Absolute Number And Average So...mentioning
confidence: 99%
“…Hypothermia does not significantly reduce brain damage primarily by reducing energy depletion and increasing intracellular calcium ion levels [ 72 ]. In a study of HIE in term newborns and stroke in adults, MSCs played a major role in boosting the proliferation and differentiation of nerve cells and regulating or suppressing the local immune response of microglia and T lymphocytes [ 73 ]. In addition, MSCs and exosomes secreted by hPSCs may be a promising treatment for neuronal injury by interacting with parenchymal cells in the brain, resulting in reduced expression of axonal inhibitors and increased production of neuroprotective factors, thereby affecting axonal growth and promoting the restoration of normal nerve function [ 74 ].…”
Section: Application Of Scs In Refractory Diseases Of Newbornsmentioning
confidence: 99%
“…Studies have shown that delayed administration (1 week after HIE) of large doses of BM-MSCs (7.5 × 10 5 –1.0 × 10 6 cells) can restore neurons projected from the striatum and improve motor function [ 80 ]. Other studies have suggested that delaying the administration of double high doses of hADSCs (PN14, PN16, ih, 1.07 × 10 6 , qd) in HIE rats significantly increases the absolute number of dorsal striatum dopamine and cyclic adenylate-regulated phosphoprotein-positive spinel neurons to normal undamaged levels [ 73 ]. Donega et al found that MSCs could be found at the site of injury 10 days after HIE, but not at 17 days, proving that the SC treatment window is at least 10 days, significantly extending the time window for hypothermia and bringing more hope for children with HIE [ 81 ].…”
Section: Application Of Scs In Refractory Diseases Of Newbornsmentioning
confidence: 99%